ASSESSMENT OF DESIRED COMPETENCIES OF AGRICULTURAL EXTENSION AGENTS IN SUSTAINABLE AGRICULTURE DEVELOPMENT ACTIVITIES IN SOUTHWEST NIGERIA - Olabode Stephen ALABI; Adedayo Olufemi AJAYI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Agricultural Extension Agents (AEAs) in Nigeria are saddled with the responsibility of helping farmers improve their knowledge and skill in agriculture thereby improving their livelihood opportunities. Based on this the study looked into the effectiveness of the agents in ensuring sustainable agricultural development. Specifically the study described the socio-economic characteristics of the AEAs, determined their levels of knowledge and skills in sustainable agricultural development activities and identified their training needs. Three states: Lagos, Oyo and Ondo states were randomly selected from the six in southwest Nigeria and all the AEAs in the Agricultural Development Projects in the selected states were sampled. Data were collected using a validated questionnaire. Data analysis was done using appropriate descriptive and inferential statistics. Results of the study revealed that males (68.1%) dominated extension service in southwest Nigeria. The mean age of the AEA was 39 years and the mean year of experience of the AEA was 10 years. AEAs highest mean score on knowledge in sustainable agricultural development activities was recorded in livestock manure management (x = 3.37) and the highest mean score in skill was recorded in farmers organization establishment (x = 2.98). Some of the training needs identified included participatory needs analysis and livestock manure management. The study concluded that many of the identified training needs are outside the pre-service training of the AEAs.